The nexus of artificial intelligence literacy collaborative knowledge practices and inclusive leadership development among higher education students in Bangladesh China Finland and Turkey - Muhammad Zaheer Asghar; Javed Iqbal; Fatih Mutlu Özbilen; Joinal Abedin; Hanna Järvenoja; Ultra Widanapathirana (Discover Computing)
Abstract This study investigates how Artificial Intelligence Literacy (AIL) fosters Inclusive Leadership (IL) development among university students through Collaborative Knowledge Practices (CKP), with cross-cultural insights from Bangladesh, China, Finland, and Turkey. Using a mixed-methods design—combining quantitative surveys of 458 students and qualitative interviews with 40 participants, this research integrates three frameworks: (1) the ABC-E model of AIL, encompassing affective, behavioral, cognitive, and ethical dimensions; (2) CKP, which involves competences such as collaboration, integration, creativity, sustainability, adaptability, engagement, and technological aspects; and (3) IL principles. Cultural interpretations are informed by Hofstede’s six-dimensional model of national culture, with a focus on the Power Distance Index (PDI) and the Individualism–Collectivism (IDV) dimensions. Quantitative analysis employed PLS-SEM and Fuzzy Set Qualitative Comparative Analysis (fsQCA) to uncover linear and non-linear relationships, while qualitative findings supported the multi-group analysis. Cross-cultural comparisons revealed that Finland emphasizes ethical AI use, China highlights innovation, Bangladesh focuses on problem-solving applications, and Turkey reflects multicultural collaboration—each of which influences students’ engagement with AI tools in distinct ways. The findings underscore CKP as a critical bridge between AIL and IL, highlighting the need for context-sensitive, collaborative pedagogies that equip students to address AI-driven challenges and lead inclusively in diverse global settings.